The taming of New York's Washington Square : a wild civility - Goode, Erich (New York University Press, 2018)
"With rich and detailed observations as well as in-depth interviews, Goode demonstrates how onlookers, bystanders, and witnesses--both denizens and your average casual park visitor--provide an effective system of social control, keeping more serious wrongdoing in check. Goode also profiles the parks visitors, showing us that the park is a major draw to residents and tourists alike. Visitors come from all over; only a quarter of the park's visitors live in the neighborhood (the Village and SoHo), one out of ten are tourists, and one out of six are from upper Manhattan or the Bronx. Goode looks at the patterns of who visits the park, when they come, and, once in the park, where they go. Regardless of where they live, Goode argues, all of the Park's visitors help keep the park safe and lively."--Provided by publisher